2020
DOI: 10.3390/ma13204637
|View full text |Cite
|
Sign up to set email alerts
|

Creep Testing of Thermoplastic Fiber-Reinforced Polymer Composite Tubular Coupons

Abstract: Thermoplastic fiber-reinforced polymer composites (TP-FRPC) are gaining popularity in industry owing to characteristics such as fast part fabrication, ductile material properties and high resistance to environmental degradation. However, TP-FRPC are prone to time-dependent deformation effects like creep under sustained loading, which can lead to significant dimensional changes and affect the safe operation of structures. Previous research in this context has focused, mainly, on testing of flat coupons. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 45 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Doan and Mertiny studied the creep response of FRTP components fabricated using FW with hot air blower ISC [108]. Glass/HDPE prepreg tapes with a width of 49 mm were used.…”
Section: Studies On Factors Affecting In Situ Consolidation Qualitymentioning
confidence: 99%
“…Doan and Mertiny studied the creep response of FRTP components fabricated using FW with hot air blower ISC [108]. Glass/HDPE prepreg tapes with a width of 49 mm were used.…”
Section: Studies On Factors Affecting In Situ Consolidation Qualitymentioning
confidence: 99%
“…Katouzian et al [ 6 ] employ the MT method to study the response of viscoelastic composites vs. the time compared with the experiment data. Moreover, Yang et al [ 7 , 8 , 9 ] experimentally studied the long-term creep behavior of fiber-reinforced composite tubes subjected to flexural loading. Martynenko et al [ 10 , 11 ] conduct numerical simulations and experiments to investigate the effect of the temperature and the lasting time on the effective viscoelasticity of fiber-reinforced composites.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that the manufacturing process using FRTP could reduce molding costs, and showed comparable strength and elastic modulus to conventional CFRP and GFRP. To develop and apply FRTPs to engineering fields, research for the evaluation of mechanical characteristics by Doan [13] and Cao [14] was carried out, and manufacturing processes were also evaluated in recent years by Fan [15] and Rodonò [16].…”
Section: Introductionmentioning
confidence: 99%